The effect of different target temperatures in targeted temperature management on neurologically favorable outcome after out-of-hospital cardiac arrest: A nationwide multicenter observational study in Japan (the JAAM-OHCA registry) - Irisawa, Taro; Matsuyama, Tasuku; Iwami, Taku; Yamada, Tomoki; Hayakawa, Koichi; Yoshiya, Kazuhisa; Noguchi, Kazuo; Nishimura, Tetsuro; Uejima, Toshifumi; Yagi, Yoshiki; Kiguchi, Takeyuki; Kishimoto, Masafumi; et al. (Resuscitation, 2018)
It has been insufficiently investigated whether neurological function after out-of-hospital cardiac arrest (OHCA) would differ by 1 °C change in ordered target temperature of 33–36 °C among patients undergoing targeted temperature management (TTM) in the real-world setting. This nationwide hospital-based observational study (The Japanese Association for Acute Medicine-OHCA Registry) conducted between June 2014 and December 2015 in Japan included OHCA patients aged ≥18 years who were treated with TTM. The primary outcome was one-month survival with neurologically favorable outcomes defined by cerebral performance category 1 or 2. To investigate the effect of TTM by 1 °C change in ordered target temperature of 33–36 °C on each outcome, random effects logistic regression analyses were performed. The final analysis included 738 patients. The proportion of patients with neurologically favorable outcome was 30.4% (7/23), 31.7% (175/552), 28.9% (11/38), and 30.4% (38/125) in the 33 °C, 34 °C, 35 °C, and 36 °C groups, respectively. In the multivariable logistic regression analysis, no group had a higher proportion of neurologically favorable outcome compared with the 34 °C group (vs. 33 °C group, adjusted odds ratio [AOR] 0.90; 95% confidence interval [CI] 0.25–3.12, vs. 35 °C group, AOR 1.17; 95% CI 0.44–3.13, vs. 36 °C group, AOR 1.26; 95% CI 0.78–2.02). In this population, we evaluated the difference in outcomes after adult OHCA patients received TTM by 1 °C change in ordered target temperature of 33–36 °C and demonstrated that there was no statistically significant difference in neurologically favorable outcomes after OHCA irrespective of target temperature.